3.3 Agricultural Science. Effects of Ce and Methanol on Growth and Expression of Methanol Dehydrogenase of Bradyrhizobium japonicum USDA110 and Its Enzymatic Properties - Kurniawati, Novita; Matsunaga, Mika; Pertiwiningrum, Ambar; Tomonori, Iwama; Kawai, Keiichi (2010)
Abstract. Rare earth elements (REEs) have been widely used in high-technology products such as computers, mobile telephones, plasma displays, magneto-optical disks, high-powered lasers fluorescent lamps and hybrid cars (1). Increasing demand of REEs may cause the environmental pollution by these elements. Despite importance of physics and chemistry of REEs, the significance of REEs in biology has been overlooked. In our laboratory, during the study on the relationships between REEs and microorganism we isolated a soil bacterium, identified as Bradyrhizobium sp. CE-3 whose methanol dehydrogenase (MDH) activity in crude cell-free extract was increased several times when grown in 1/10 nutrient medium containing Ce. This is of interest that REEs exhibited the physiological effects on enzyme expression of microorganisms. Bradyrhizobium japonicum USDA110 has been widely used as standard to investigate the physiological, biochemical and genetic characterizations of the genus Bradyrhizobium. Kaneko et al. published the complete genomic nucleotide sequence of B. japonicum USDA110 and pointed out that this bacterium has a gene encoding a MDH large subunits-like protein at blr locus 6213 (2). In this report, I describe the effects of Ce and methanol on growth and expression of MDH activity of B. japonicum USDA 110, and that purification and some properties of the enzyme. Growth behaviors and MDH activity: The 1/10 diluted nutrient medium was used in this study. Methanol and Ce were added at 0.5% and 30 μM, respectively. Bacterium was cultured with rotary shaker (120 rpm) at 300 Growth of B. japonicum USDA110 exhibited remarkable increase in the presence of both 30 μM Ce and 0.5% methanol. This results suggest that Ce is important role in methanol metabolism of the genus Bradyrhizobium. In addition, activity of MDH was remarkably increased by Ce and methanol. MDHs of Methylobacterium spp. were found to increase several times by Ce. It seems that Ce is involved in induction of MDHs of methylotrophic bacteria. C. Cells were harvested by centrifugation, washed with 20mM Tris-HCl buffer (pH 8.0), and suspended in the same buffer. Cells were disrupted by sonication. After centrifugation, the supernatant was used as cellfree extract. Activity of MDH was determined according to method of Day and Anthony (3). Protein concentration was determined by using BCA Protein Assay Kit. Purification of MDH: Ce-induced MDH was purified by three purification steps. The enzyme was purified 16 fold with yield of 7% and migrated as a single band (67 kDa) on SDS-PAGE (4). Properties of purified MDH: By gel chromatography MW of native MDH was estimated to be approximately 86 kDa. This result suggests that the MDH was monomer. Recently the monomeric MDH which was a product of xoxF (synonym mxaF’) gene of Methylobacterium extorquens AM1 was reported (5). The enzyme was more active to primary alcohols such as ethanol (93%), 1-Propanol (93%), and 1-butanol (93%) rather than secondary alcohols such as 2-propanol (36%) and 2-buthanol (36%), relative to methanol (100%). The pH and temperature optimum was 9.0 and 35C, respectively. Km for methanol and Vmax were determined to be 0.32 mM and 11.0 U/mg protein by Lineweaver-Burk plots. The N-terminal amino acid sequence was determined to be 1-NDELHKMAQNPKDWVMP-17. The amino acid sequence was highly identity to that of deduced amino acid sequence of MDH large subunit-like protein encoded by mxaF’ (3). Keywords: Ce, methanol dehydrogenase, Bradyrhizobium japonicum, methanol